2017
DOI: 10.35808/ersj/609
|View full text |Cite
|
Sign up to set email alerts
|

The Development of Cluster Relations within the State and Business Structures in Terms of Strategy of Non-Primary Sector Import-Substitution

Abstract: The main aim of the article is to determine how the implementation of the strategy of import substitution in non-primary sector of the Russian economy can be insured. Rostov region and other Southern regions of Russia were selected as the subjects of the study by the authors. Research particularly focuses on the main areas of socioeconomic development as well as the process of implementation of the import substitution policy. The authors also analyzed the possibility of solving the problems of import substitut… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
19
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(20 citation statements)
references
References 6 publications
(5 reference statements)
0
19
0
1
Order By: Relevance
“…Some authors detail the main stages of managing environmental and economic risks, highlighting in independent sections the definition of the structure of possible damage and graphical representation of the law of its distribution. In this case risk management is the formation of a prototype decision base, taking into account the control of risk exposure measures [5].…”
Section: Management Of Ecological and Economic Risksmentioning
confidence: 99%
See 1 more Smart Citation
“…Some authors detail the main stages of managing environmental and economic risks, highlighting in independent sections the definition of the structure of possible damage and graphical representation of the law of its distribution. In this case risk management is the formation of a prototype decision base, taking into account the control of risk exposure measures [5].…”
Section: Management Of Ecological and Economic Risksmentioning
confidence: 99%
“…Persons making decision on these tasks periodically face the need for an integrated assessment of the potential of innovative projects. When carrying out such an examination, a large number of functional indicators [5] (mining-geological, technological, technical, economic, ecological, social) must be taken into account, which may have a different naturequantitative and qualitative. Thus, an important task is the formation of methods and algorithms for evaluating of ecological and economic risks of mining enterprises which allow taking into account the maximum possible number of factors associated with the implementation of innovation with minimal time, labor costs and a low proportion of subjectivity.…”
Section: Introductionmentioning
confidence: 99%
“…Travel vehicles, hotels, restaurants, shopping centres, sightseeing areas are the areas where tourist and residents meet most. Tezcan (2012) and Rocharungsat (2004) summarize the conditions that could result from the interactions between tourists and residents as follows (Sarı et al, 2009;Tyaglov et al, 2017;Sibirskaya et al, 2016;Kovalenko et al, 2016;Ryzhkova and Prosvirkin, 2015;Epifanova et al, 2015):…”
Section: Introductionmentioning
confidence: 99%
“…Many experts and producers presented evidence that their experience of growing and consuming GM products had shown that such agricultural technology did not lead to yield increase. What is more, they caused uncontrollable use of pesticides in attempt to maintain agricultural productivity (Yermakova, 2014;Borisova et al, 2015;Tyaglov et al, 2017;Polychronidou et al, 2014).…”
Section: Introductionmentioning
confidence: 99%